2012
DOI: 10.1161/strokeaha.112.661819
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protease-Activated Receptor-1 in Brain Injury After Experimental Global Cerebral Ischemia

Abstract: Background Evidence suggests that the protease-activated receptor-1 (PAR-1), a thrombin receptor, mediates neuronal injury in experimental cerebral ischemia. The present study investigated whether PAR-1 plays a role in brain injury after global cerebral ischemia. Methods Adult male wild type (WT) or PAR-1 knockout mice underwent a 20-minute bilateral common carotid artery occlusion (BCCAO) or a sham operation. Behavior tests were performed before ischemia, and 1, 2 and 3 days after BCCAO. Mice were euthanize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 33 publications
(42 reference statements)
2
36
1
1
Order By: Relevance
“…A reduction in mitochondrial complex I or IV activity may lead to mitochondrial respiratory chain deficiency and may result in ROS overproduction [34][35][36]. Compared with the IR group, PTE treatment significantly increased the MMP (Fig.…”
Section: The Effects Of Pte On Mitochondrial Oxidative Damage Indicatmentioning
confidence: 95%
See 2 more Smart Citations
“…A reduction in mitochondrial complex I or IV activity may lead to mitochondrial respiratory chain deficiency and may result in ROS overproduction [34][35][36]. Compared with the IR group, PTE treatment significantly increased the MMP (Fig.…”
Section: The Effects Of Pte On Mitochondrial Oxidative Damage Indicatmentioning
confidence: 95%
“…As described previously [34], right hemisphere and left hemisphere were obtained for further detection. Tissue samples were immediately weighed to obtain the wet weight.…”
Section: Brain Water and Ion Content Assay In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal cell death is restricted to sensitive areas of brain, such as the striatum (Wang et al 2012;Yoshioka et al 2011a;Yoshioka et al 2011b). In this study, Cresyl violet and TUNEL staining carried out to detect brain damage revealed that the C57BL/6 mice model showed remarkable neuronal damage in the striatum after 24 h of reperfusion and 5-HMF significantly ameliorated pathological injury of the striatum.…”
Section: Discussionmentioning
confidence: 66%
“…The hippocampus receives much attention (Soares et al 2016;Takeuchi et al 2015), but the striatum has not been well studied. Evidence suggests that the striatal neurons are vulnerable to tGCI, as are hippocampal CA1 neurons, and tGCI produces consistent striatum injury (Wang et al 2012;Yoshioka et al 2011a;Yoshioka et al 2011b). The neuronal loss shows a close correlation with the deficits in neurological function, which are similar to clinic symptoms caused by neurological disorders, such as stroke (Ernst et al 2014;Lindvall and Kokaia 2006).…”
Section: Introductionmentioning
confidence: 99%